Effect of packaged tea drinks consumption to corrosion rate of stainless steel orthodontic wire - Mansjur Nasir; Rafiqah R. Amelia (Journal of Dentomaxillofacial Science, 2021)
Objective: To determine the effect of packaged tea drinks consumption to corrosion rate of stainless steel orthodontic wire.Material and Methods: This study is laboratory experimental with post-test only with control group design using stainless steel orthodontic wire with total of 16 samples. The wire length is 6 cm and diameter is 0.41 mm. Samples were divided into 4 groups with 1 group of artificial saliva and 3 groups with a packaged tea drinks substitution. Measurement of corrosion rate was done by using potensiostat tool and data analysis using SPSS version 23 and ANOVA test with significant value of p<0.05.Results: Jasmine and fruit flavor packaged tea group had lower corrosion rate value than the control group. While green packaged tea group had higher corrosion rate value than the control group.Conclusion: Green packaged tea drinks had the biggest effect on corrosion rate of stainless steel orthodontic wire.